2022
DOI: 10.3390/pharmacy10030060
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Driven Improvements and Innovations in Pharmacy Education: A Scoping Review

Abstract: The COVID-19 pandemic led to many colleges of pharmacy having to make major changes relating to their infrastructure and delivery of their curriculum within a very short time frame, including the transition of many components to an online setting. This scoping review sought to summarize what is known about the impact of COVID-19 on pharmacy education and the effectiveness of adaptation strategies which were put in place. PubMed, Web of Science, OVID Medline, and MedEdPortal were searched to identify pharmacy e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Globally, 39 papers and 1 report were selected: PubMed (n = 33) [ 10 , 13 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], SciELO (n = 1) [ 52 ], Google Scholar (n = 6) [ 8 , 53 , 54 , 55 , 56 , 57 ], and sites of known international organizations (n = 1) [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, 39 papers and 1 report were selected: PubMed (n = 33) [ 10 , 13 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], SciELO (n = 1) [ 52 ], Google Scholar (n = 6) [ 8 , 53 , 54 , 55 , 56 , 57 ], and sites of known international organizations (n = 1) [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…The selected publications were classified as follows: 7 reviews [ 8 , 13 , 23 , 41 , 43 , 52 , 53 ]; 31 original research publications [ 10 , 21 , 22 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 42 , 44 , 45 , 46 , 48 , 49 , 50 , 51 , 55 , 56 , 57 ]; 1 commentary [ 47 ]; 1 case study [ 54 ]; 1 report [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, some of the participants still felt that essential elements of the rotation experience were missing. As such, the integration of telemedicine is beginning to be at the forefront of many health professions programs, and should be considered into the contingency plans for psychiatric rotations in case of future emergencies [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Since the pandemic, online-based learning has become mainstream in many countries, and its learning outcomes have been evaluated [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. A scoping review reported in 2022 aimed to summarize the findings on the impact of COVID-19 on pharmacy education and the effectiveness of the real-world response measures [ 10 ]. However, while these reports indicate that online-based learning needs to be optimized in the future [ 3 ], the number of reports required for this purpose is not sufficient.…”
Section: Introductionmentioning
confidence: 99%